Asuhan Keperawatan Keluarga Ny. M Dengan Masalah Keperawatan Utama Nyeri Akut Pada Hipertensi di Puskesmas Sumbang I - Utami, Ristanti Dwi; Maryoto, Madyo; Rahmawati, Arni Nur (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Hypertension is a disease caused by very high blood pressure in the blood vessels which are the carriers of the heart which pumps blood to all tissues and organs of the body. Every increase of 20 mmHg in systolic blood pressure or 10 mmHg in distolic blood pressure can increase the risk of death from ischemic heart disease and stroke. One of the nursing problems that can be found in hypertensive clients is acute pain. The aim of this research is to provide family nursing care to acute hypertensive pain patients at the Sumbang 1 Banyumas Community Health Center. The design of this research is a descriptive case study approach of nursing care starting from assessment, diagnosis, planning, nursing intervention, nursing implementation, and evaluation. Participating in this research were two people, one suffering from acute hypertension pain and the second was his family. Data collection techniques in this research were carried out using observation, interviews and documentation studies. The results of this research showed that families with hypertensive clients could be diagnosed with the main disease, namely acute pain, and the treatment intervention chosen was pain management. Conclusion: implementation of acute pain management: deep breathing relaxation techniques and murotal distraction techniques are not good for treating acute pain in hypertensive clients during 3 days of treatment.